Half day seminar on " Failure in structures - Learning from the structural failures and mistakes of Structural Engineers" - Ong, Sang Woh, Ir. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/